2011
DOI: 10.1177/0093854810397449
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Frequency of Intimate Partner Violence By Male Perpetrators

Abstract: The authors measured potential causes of prolonged male violence against female intimate partners in four domains: enduring antisocial traits, perpetrator's attitudes and values, aspects of the relationship, and neighborhood characteristics. They also examined perpetrators' substance abuse and the couples' socioeconomic status as possible causes of prolonged intimate partner violence. The dependent variable was the total number of instances of violence against a female intimate partner recorded for each male p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 115 publications
4
16
0
Order By: Relevance
“…Similar conclusions may be extended to the antisocial/violent group. This group was labelled in the literature as a "high risk group" (Cavanaugh & Gelles, 2005), as antisocial behaviour is connected with intimate partner violence (Hilton, Harris, Rice, Houghton, & Eke, 2008;Harris, Hilton, & Rice, 2011). Consequently, some authors argue that antisocial batterers may benefit from an integral intervention with a multimodal focus, i.e., a cognitive and behavioural approach, and a multilevel focus, i.e., directed to the batterer and to the other areas related to intimate partner violence in which there are deficits (e.g., family, social network, community, job training) (Arce & Fariña, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions may be extended to the antisocial/violent group. This group was labelled in the literature as a "high risk group" (Cavanaugh & Gelles, 2005), as antisocial behaviour is connected with intimate partner violence (Hilton, Harris, Rice, Houghton, & Eke, 2008;Harris, Hilton, & Rice, 2011). Consequently, some authors argue that antisocial batterers may benefit from an integral intervention with a multimodal focus, i.e., a cognitive and behavioural approach, and a multilevel focus, i.e., directed to the batterer and to the other areas related to intimate partner violence in which there are deficits (e.g., family, social network, community, job training) (Arce & Fariña, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, research on male batterers have suggested that in most cases of severe IPV against women male aggressors were also generally violent beyond the family realm (Cavanough & Gelles, 2005;Fowler & Westen, 2011;Gondolf, 1988;Hamberger, Lohn, Bonge, & Tonlin, 1996;Harris, Hilton, & Rice, 2011;Holtzworth-Munroe & Stuart, 1994). As Herrero, Torres, Fernández-Suárez, & Rodríguez-Díaz (2016) have recently suggested, however, the fact that severe IPV against women is overrepresented in penitentiary-based samples of male batterers might lead to a lack of representativeness of the less violent batterer.…”
Section: Batterers In Prisonmentioning
confidence: 99%
“…Twenty-six studies examined the role of psychopathy to predict IPV perpetration among non-convicted partner-violent men (see Table 3; Babcock, Green, & Webb, 2008;Babcock, Green, Webb, & Yerington, 2005;Bates, Archer, & Graham-Kevan, 2017;Coyne, Nelson, Graham-Kevan, Keister, & Grant, 2010;Holtzworth-Munroe, Meehan, Herron, Rehman, & Stuart, 2000;Iyican, Sommer, Kini, & Babcock, 2015;Kiire, 2017;Mager, Bresin, & Verona, 2014;Marshall & Holtzworth-Munroe, 2010;Okano, Langille, & Walsh, 2016;Panuzio et al, 2006;Theobald, Farrington, Coid, & Piquero, 2015;Thornton, Graham-Kevan, & Archer, 2016;Walsh et al, 2010;Wymbs, Dawson, Suhr, Bunford, & Gidycz, 2017) and convicted male batterers (see Table 4; Cunha & Gonçalves, 2013;Harris, Hilton, & Rice, 2011;Hilton, Harris, & Rice, 2001;Hilton, Harris, Rice, Houghton, & Eke, 2008;Hornsveld, Bezuijen, Leenaars, & Kraaimaat, 2008;Juodis, Starzomski, Porter, & Woodworth, 2014a;Kalichman, 1988;Rock, Sellbom, Ben-Porath, & Salekin, 2013;Swogger, Walsh, & Kosson, 2007;Swogger, Walsh, Kosson, Cashman-Brown, & Caine 2012;Taft, Murphy, Musser, & Remington, 2004). …”
Section: •The Role Of Psychopathy To Predict Male-to-female Ipv Perpementioning
confidence: 99%
“…•EVIDENCE FROM STUDIES CONDUCTED WITH CONVICTED MALE BATTERERS Again, among convicted male batterers, most studies evidenced a significant positive small-to-moderate correlation (.22 ≤ r ≤ .39) between psychopathy and male-to-female IPV perpetration (Harris et al, 2011;Hilton et al, 2008;Rock et al, 2013;Taft et al, 2004).…”
Section: •Evidence From Studies Conducted With Non-convicted Partner-mentioning
confidence: 99%